Analisis implementasi pernyataan misi bank syariah indonesia berdasarkan pendekatan swot - Ar-Rifa'i, Fahmi Amru (Maliki Interdisciplinary Journal, 2025)
Fierce competition among companies, coupled with rapid changes in consumer behavior, requires companies to have a clear strategic direction. Strategic management plays an important role in determining the long-term strategic direction formulated in the company's mission, which reflects its long-term direction and goals. Bank Syariah Indonesia has a fairly good mission statement, covering almost all components of mission statement evaluation. This study uses a descriptive-qualitative method, with the object of research being the implementation of the mission statement of Indonesian Islamic Banks, while the subject of research includes an analysis of internal and external factors through a SWOT approach. The data used is secondary data, and the data collection technique is documentation. This study aims to determine the extent to which the mission statement of Bank Syariah Indonesia has been implemented and to provide strategic recommendations that can accelerate the realization of the mission based on current conditions in the field using the SWOT approach. The results of this study provide an overview of the progress made in several of BSI's mission statements and strategic recommendations based on SWOT analysis to accelerate the realization of missions that have not yet been realized.